Comparative Assessment of Sperm Morphology in Liquid-Preserved Boar Semen Using Cytological Stains - Braune, Annika; Wehrend, Axel; Kauffold, Johannes; Farshad, Abbas; Justus Liebig University Giessen (My University, 2025)
Accurate assessment of sperm morphology is essential for artificial insemination using liquid-preserved boar semen. This study compared nine commonly used staining techniques, eosin, eosin–nigrosin, Diff-Quick®, Hemacolor®, Sangodiff-G®, Spermac®, Formol–Citrate–Rose Bengal stain, Testsimplets®, and Methyl Violet, based on morphological assessment, cost, time efficiency, and storage stability. Each staining method was applied to 36 slides, totaling 324 samples, and evaluated four times each (1296 evaluations). Slides were analyzed four times: immediately after staining and after 1 day, 1 week, and 3 months of storage. The results indicated that Eosin was the fastest and most cost-effective method, providing strong contrast, though it increased detection of structural alterations. Eosin–nigrosin offered detailed morphology but formed colored crystals over time. Diff-Quick® and Hemacolor® showed good initial performance, but Hemacolor® lost pigment clarity after 3 months (p = 0.0273). Sangodiff-G® had poor contrast and reduced detection of abnormalities (p = 0.00229). Spermac® delivered high contrast but was time-consuming. Formol–Citrate–Rose Bengal stain required extensive preparation and showed significant post-storage changes (p < 0.0001). Testsimplets®, despite their high cost, suffered from declining interpretability (p < 0.0001). Methyl Violet lacked sufficient resolution and was highly unstable over time (p < 0.0001). In conclusion, Eosin emerged as the most practical and economical staining method for routine morphological evaluation of liquid-preserved boar semen. While eosin–nigrosin was also effective, its storage instability limits broader application. Other methods showed specific weaknesses, emphasizing the need to tailor stain selection to laboratory goals and constraints.
Keywords: ddc:630